BENTUK DAN PENGGUNAAN KATA PENGGOLONG BENDA DI PASAR INDUK TRADISIONAL DI JAKARTA DAN SURABAYA - Nadra Nadra; Sri Wahyuni; Mahsun Mahsun (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe forms of noun classifiers and their uses by Indonesianspeakers in transactions in traditional central markets in Jakarta and Surabaya. The datawere collected through listening and interviewing. They were analyzed by the intralingualcorrespondence technique. The research findings are as follows. First, there are43 forms of noun classifiers. Second, they can be classified into three categories, i.e.: (a)individual noun classifiers, (b) collective noun classifiers, and (c) noun classifiers in theform of measurement units. Third, the dominant noun classifiers in traditional centralmarkets in Jakarta and Surabaya are noun classifiers in the form of measurement units.This is due to the fact that transactions need precise measurements.